2019
DOI: 10.3390/coatings9020094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene on Flame Retardancy of Graphite Doped Intumescent Flame Retardant (IFR) Coatings: Synergy or Antagonism

Abstract: A comparative study between graphene and modified graphene oxide (mGO) on the flame retardancy of graphite doped intumescent flame retardant (IFR) coatings is preliminarily investigated by cone calorimeter (CC), XRD, and SEM, with the final aim of clarifying the interactions between different graphenes and graphite doped coatings (polyester resin-ammonium polyphosphate-urea-pentaerythritol). The CC results determine that graphene exerts an obviously antagonistic effect on flame resistance, evidenced by the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Table 2 briefly summarizes the combustion parameters of samples during the whole combustion process. Because the FGI and FPI are the most important indicators to evaluate the flashover propensity of combustible materials, 3‐5 which is consensual and widely used‐avenue to analyze this issue. Meanwhile, the S2 exhibits the lowest p‐HRR of 111.9 kW m −2 and FGI of 0.45 kW m −2 s −1 , as well as the highest FPI of 0.71 second·m 2 kW −1 and residue weight of 40.55 wt% among all samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 briefly summarizes the combustion parameters of samples during the whole combustion process. Because the FGI and FPI are the most important indicators to evaluate the flashover propensity of combustible materials, 3‐5 which is consensual and widely used‐avenue to analyze this issue. Meanwhile, the S2 exhibits the lowest p‐HRR of 111.9 kW m −2 and FGI of 0.45 kW m −2 s −1 , as well as the highest FPI of 0.71 second·m 2 kW −1 and residue weight of 40.55 wt% among all samples.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 However, the flame resistance of IFRCs needs to be further improved before being in extensive applications, and also the water-resistance and opacity of hybrid coating need to be optimized simultaneously. Our previous investigations have attempted to enhance the flame resistance of IFRCs by incorporating inorganic silicate 3 or graphite, 4,5 but the coating color is inherent gray and non-transparent. Meanwhile, the main methodologies developed to fabricate transparent nanocomposites mainly contain four categories: the blending of nanoparticles and transparent polymer; the in-situ polymerization in the presence of pre-formed nanoparticles; the in-situ nanoparticle synthesis in a pre-formed polymer matrix; and finally the simultaneous polymerization and in situ nanoparticle synthesis.…”
mentioning
confidence: 99%
“…The thickener and film-forming agent, polyacrylamide (PAM), was synthesized by the Shanghai reagent factory in China. EG served as the charring fortifier [15] and was fabricated by the Qingdao chemical group in China with a volume-expansion rate of 300 mL•g −1 and an average particle size of 48 µm. The second-class flame-retarding plywood was produced in the Xi'an timber processing plant.…”
Section: Starting Materialsmentioning
confidence: 99%
“…The heat release rate (HRR), time to ignite (TTI), the peak heat release rate (pHRR), time to pHRR (T p ), O 2 concentration and smoke temperature in exhaust smoke, and time to the cessation of flaming (T b ) were recorded in real time. The fire performance index (FPI, FPI = TTI/pHRR) and fire growth index (FGI, FGI = pHRR/T p ), were the most important indexes to distinguish the flame-retardant efficiency [7,13,15], the sample with a higher FPI and lower FGI corresponded to a stronger flame resistance.…”
Section: Flame Resistancementioning
confidence: 99%
“…[ 17,18 ] It is reported that graphene and GO at very low loadings (less than 1 wt%) can provide significant mechanical reinforcement to materials used to provide high FR. [ 19‐22 ] GO has been demonstrated that imparts FR characteristics to polymer composites mainly because it can improve the polymer thermal stability and delay its ignition. It also can inhibit fire from spreading and reduce the heat release rate (HRR).…”
Section: Introductionmentioning
confidence: 99%